Analisis Faktor-faktor yang Paling Dominan Mempengaruhi Kepuasan Konsumen Pada Toko Bahan Bangunan Umran Jaya Abadi Muara Bulian - Ratumas Hartha Delima (CITRA EKONOMI, 2020)
Marketing is a combination of activities that are interconnected to determine the needs of consumers and develop promotion, distribution, services and price. So that consumers can be properly satisfied at a certain level of needs. The purpose of this study is to explain the effect to product quality, price and service quality on consumer satisfaction in the Material Store Building Umran Jaya Abadi Muara Bulian. The analytical methode used is qualitative, the data used are primary and secondery data, the analitycal tool used is the validity test, reliability test, multiple linear regression tools. Testing the significance of the influence of product quality variabels (X1), price (X2), and service quality (X3) as independent variabels, and customer satisfaction Y as the dependent variabels by t test, f test and determination. Based on the result of the research, the component that influences dominant factor is services quality , which has the highest vvalue of 4,663 compared to the product quality factor 4,440 the price factor is 1,759. While the adjust R Square obtained a value of 0,45 or 45% meand that product quality, price and services consunmer satisfaction by 45%.